2005
DOI: 10.1007/s00405-005-1002-6
|View full text |Cite
|
Sign up to set email alerts
|

Hearing results with the titanium ossicular replacement prostheses

Abstract: The purpose was to study the hearing results in patients receiving a Kurz titanium Bell partial ossicular replacement prosthesis (PORP) or an Aerial total ossicular replacement prosthesis (TORP). The study was a retrospective chart review in a tertiary otologic referral center. A computerized otologic database was used to identify 111 patients implanted with either a PORP or TORP prosthesis. Audiograms were reviewed and air-bone gaps were calculated for each patient. The improvement of the average air-bone gap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
76
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(98 citation statements)
references
References 31 publications
15
76
7
Order By: Relevance
“…A wide range of values of ABG improvement with various types of PORP and TORP has been reported. Concerning titanium prosthesis, although most studies report that PORP outperform TORP [2][3][4]16], some series [1,14,17] report no significant difference between both types of reconstruction or even better results with TORP [12]. This suggests that the quality of mechanical coupling between TORP titanium prosthesis and the footplate is adequate.…”
Section: Discussionmentioning
confidence: 85%
“…A wide range of values of ABG improvement with various types of PORP and TORP has been reported. Concerning titanium prosthesis, although most studies report that PORP outperform TORP [2][3][4]16], some series [1,14,17] report no significant difference between both types of reconstruction or even better results with TORP [12]. This suggests that the quality of mechanical coupling between TORP titanium prosthesis and the footplate is adequate.…”
Section: Discussionmentioning
confidence: 85%
“…The success rates of other otologic surgeons who used the same implants were for House and Teufert [12] 61 and 69% for TORP and PORP, respectively, and for Slater et al [13] they were 69 and 45%, respectively. Schmerber et al [14] , using titanium ossicular replacement prostheses, found ABG closure to within 20 dB or less in 77% of the cases in the PORP group, versus 52% of the cases in the TORP group. In a recent, very informative study, Truy et al [15] reported similar ABG values in four subgroups (TORP vs. PORP and hydroxyapatite vs. titanium).…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported high biocompatibility of these implants, with extrusion rates lower than 5% and good hearing results, and with average postoperative air-bone gap (ABG) ranging from 14 to 21 dB and postoperative ABG lower than 20 dB in 56-77% of cases [4][5][6][7][8][9][10][11]. The described advantages of titanium over other materials are its tensile strength, light weight and mass, and biocompatibility [3][4][5][6].…”
Section: Introductionmentioning
confidence: 94%